PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DI ANGKRINGAN D’JUGURAN PURBALINGGA - Rindang Pambudi, Fajar; Pratiwi, Agustin Riyan; Ulya, Widadatul (Awatara Publisher, 2023)
Every businessman desires to have a large number of customers and earn maximum income with the presence of repeated purchases of products, so the purchase decision is very important for the well-being of the business. There was a Purbalingga Food Center, making the consumers of Angkringan D’juguran Purbalinda switch to make purchases in the place, so that consumers in Angringan D'juguran purbalingga suffered a decline. This research aims to find out the impact of the quality of service and price on the purchase decision in Angkringan D’juguran Purbalingga. The population in this study is all consumers who have ever made repeated purchases in D’juguran Purbalingga and the determination of the sample with the Slovin formula resulted in 96 respondents. Data collection is done using a Google form questionnaire using random sampling. The researchers used a quantitative method with a double regression analysis technique performed using the SPSS program version 26. Based on the results of this research, it was concluded that the quality of service and the price partially had a significant positive influence on the purchase decision. The result, can be used by Angkringan D’juguran Purbalingga to improve the quality of its services and provide the best price to consumers, so that consumers can make a purchase decision with maximum.